2017
DOI: 10.1021/acsbiomaterials.7b00527
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Hyaluronic Acid-Lysozyme Composite Coating on AZ31 Mg Alloy with Combined Antibacterial and Osteoinductive Activities

Abstract: This study presents the covalent grafting of a hyaluronic acid-lysozyme (HA-LZ) composite onto corrosion-resistant silane-coated AZ31 Mg alloy via EDC-NHS coupling reactions. The HA-LZ composite coatings created a smooth and hydrophilic surface with the increased concentration of functional lysozyme complexed to the hyaluronic acid. This was confirmed by the measurement of AFM, water contact angle, and quantification of hyaluronic acid and lysozyme. The colonization of S.aureus on HA-LZ composite-coated substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The AZ31-OH and Ti–OH substrates were dip-coated sequentially in MTES-TEOS (AZ31-MT or Ti-MT) and APTES (A) sol–gels and cured at 120 °C for 1 h at each step to achieve the amine-terminated AZ31-MT-A and Ti-MT-A surfaces . Furthermore, 1 mg/mL high- and low-molecular-weight HA solutions were used to functionalize AZ31-MT-A and Ti-MT-A substrates by a carbodiimide-mediated coupling reaction as detailed in the previous study. ,, The resultant high- and low-molecular HA-functionalized AZ31-MT-A or Ti-MT-A substrates are denoted as h-HA-AZ31, l-HA-AZ31, h-HA-Ti ,and l-HA-Ti substrates, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AZ31-OH and Ti–OH substrates were dip-coated sequentially in MTES-TEOS (AZ31-MT or Ti-MT) and APTES (A) sol–gels and cured at 120 °C for 1 h at each step to achieve the amine-terminated AZ31-MT-A and Ti-MT-A surfaces . Furthermore, 1 mg/mL high- and low-molecular-weight HA solutions were used to functionalize AZ31-MT-A and Ti-MT-A substrates by a carbodiimide-mediated coupling reaction as detailed in the previous study. ,, The resultant high- and low-molecular HA-functionalized AZ31-MT-A or Ti-MT-A substrates are denoted as h-HA-AZ31, l-HA-AZ31, h-HA-Ti ,and l-HA-Ti substrates, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Magnesium-based alloys have also been subjected to various surface modifications to enhance their corrosion resistance and biocompatibility . In addition, low levels of Mg 2+ released in the surrounding medium due to controlled degradation of Mg-based alloys has been shown to improve the osteoblastic activity. However, rapid degradation of Mg alloys leads to alkalization of the surrounding medium (pH >9) causing toxicity of the bone-related cells. , Previous studies employed various strategies to improve the cytocompatibility and osseointegration of Mg-based alloys using surface functionalization of biomacromolecules such as collagen, albumin, heparin, chitosan, or their composites , Our previous study showed that hyaluronic acid functionalized on treated AZ31 substrates enhanced the osteoblastic activity as compared to the bare alloy . This improved cytocompatibility is attributed to the osteoinductive property of HA and controlled degradation of the AZ31-Mg alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, no acid degradation products will be released during degradation process. In addition, other functionalities, including self-healing [ 238 ], anti-inflammation [ 240 ] and osteoinduction [ 241 ], can also be achieved when loaded with functional agents. CaP-based coatings …”
Section: Perspectives On the Future Surface Modification Strategies Of Zn-based Bmsmentioning
confidence: 99%
“…Apart from the aforementioned four kinds of biopolymers, other natural polymeric materials, like albumin, silk fibroin, cellulose, hyaluronic acid, fibrin, and so forth, have also been proposed for corrosion protection and biocompatibility promotion of Mg bio‐implants 36–40 . For instance, a hyaluronic acid‐lysozyme layer was grafted on silane‐coated corrosion resistant AZ31 Mg alloy via EDC‐NHS coupling reaction, to introduce additional antibacterial and osteoinductive functionalities 39 . Xiong et al 40 designed a pH‐sensitive self‐healing coating (Silk‐KP) on Mg‐1Ca alloy by combining silk fibroin and K 3 PO 4 through spin‐coating technique.…”
Section: Polymeric Coatings On Mg‐based Biomaterialsmentioning
confidence: 99%